ANALISIS KELAYAKAN BISNIS PENGECATAN MOTOR (STUDI KASUS DI UKM SBS GARAGE AND PAINT KOTA BATAM) - Tampubolon, Charles Bronson; Anggia Arista (Computer Science and Industrial Engineering, 2024)
Feasibility analysis of the motorbike painting business at SBS Garage and Paint UKM aims to determine the feasibility of the SBS Garage and Paint workshop business. SBS Garage and Paint workshop is in the Buana Central Park area, and wants to test whether the motorbike painting business is feasible or not. to determine the level of feasibility in terms of several aspects, namely market and marketing aspects, technical aspects, management aspects and legal aspects. The market and marketing aspects of the SBS Garage and Paint workshop are able to fulfill the marketing mix strategy (product, price, place and promotion) and the STP strategy (Segmenting, Targeting and Positioning). The technical aspects of the SBS Garage and Paint workshop have according to the criteria and being able to choose the location, layout and selection of tools, the management aspect of the SBS Garage and Paint workshop has an organizational structure and job description and the legal aspect states that the SBS Garage and Paint workshop has a business license and has met the requirements of the bank if you want to take out a business capital loan. So it can be concluded that the analysis of business feasibility in market and marketing aspects, technical aspects, management aspects, and legal aspects is feasible.